TOXIC PEOPLE DAN DAMPAKNYA DI ‎DALAM AL-QUR’AN (ANALISIS TERHADAP ‎PENAFSIRAN BUYA HAMKA DALAM TAFSIR ‎AL AZHAR)‎ - Butar Butar, Nurul Azzahra (Jurnal Ushuluddin, 2021)
This research is motivated by the issue of increasingly diverse human behaviors, diminishing morals, and a lack of empathy toward others. People often hurl harmful words at one another, impacting relationships in families, friendships, communities, and even social media. Such individuals are often labeled as "toxic," as their actions negatively affect others, causing harm. Generally, a person can be considered toxic if they bring negative influence into their surroundings, making others feel uncomfortable. The objective of this study is to analyze the verses related to toxic behavior in the Qur'an, as well as Buya Hamka's interpretation of these verses. The research method used is qualitative, based on library research, and employs a thematic interpretation (Maudu`i) approach, analyzing data from primary sources, including the Qur'an, books, and Buya Hamka's Tafsir Al Azhar. The results indicate that toxic behavior disrupts others' lives, causing harm both physically and emotionally. Several Qur'anic verses address toxic behavior, such as Surah An-Nisa (148), Al-Isra (53), Al-Hujurat (11-12), and Luqman (18-19). Buya Hamka explains in his Tafsir that Allah strictly forbids mocking, accusing, lying, or speaking ill of others, as these actions are deeply disliked by Allah. The impact of toxic behavior can be seen in three aspects: spiritual, psychological, and sociological. The core of these effects is the distancing from Allah, which leads to apathy toward others and worsens psychological well-being, trapping individuals in a toxic cycle. With such minimal morals, society will ultimately reject such individuals.